The impacts of poverty, unemployment, and divorce on child abuse in Malaysia: ARDL approach - Zaidi Yob; Mohd Shahidan Shaari; Miguel Angel Esquivias Padilla; Benjamin Nangle; Wan Zuki Azman Wan Muhamad (Economies, 2022)
The increasing number of reported child abuse cases in Malaysia is alarming, with more than 1000 cases reported every year. If this trend continues, it may have detrimental effects on children's mental development, and far-reaching negative effects for wider society. Examining whether there is some relationship between divorce, unemployment, poverty, inflation, economic growth, and child abuse in Malaysia may help shed some light on the issue and any potential solutions. This study employs the ARDL approach by using data from 1989 to 2019. The results reveal that unemployment, inflation, and economic growth have significant relationships with reported child abuse cases in the long run. However, divorce and poverty do not affect the number of reported child abuse cases in the long run. In the short run, the results show that divorce, economic growth, and unemployment can positively affect the number of reported child abuse cases. Poverty, on the other hand, has a significant and negative relationship with the number of reported child abuse cases in the short run. Family stress originating from economic and social distress and the potential inability of couples to manage stress may exacerbate the risk of child abuse in Malaysia. Social programs are likely needed to help couples handle stress at home, in the form of state-sponsored counselling, educational programs for parents, the provision of social support for an increasing number of dual-career couples, assistance for spouses dealing with divorce, and the protection of children from hostile environments at home, as well as general approaches to the alleviation of poverty.
Keywords: 330; child abuse; divorcement; economic growth; inflation; poverty; unemployment